Can cardiolipins be used as a biomarker for arbuscular mycorrhizal fungi? - Řezanka, Tomáš; Hršelová, Hana; Kyselová, Lucie; Jansa, Jan (Mycorrhiza, 2023)
Specific biomarker molecules are increasingly being used for detection and quantification in plant and soil samples of arbuscular mycorrhizal (AM) fungi, an important and widespread microbial guild heavily implicated in transfers of nutrients and carbon between plants and soils and in the maintenance of soil physico-chemical properties. Yet, concerns have previously been raised as to the validity of a range of previously used approaches (e.g., microscopy, AM-specific fatty acids, sterols, glomalin-like molecules, ribosomal DNA sequences), justifying further research into novel biomarkers for AM fungal abundance and/or functioning. Here, we focused on complex polar lipids contained in pure biomass of Rhizophagus irregularis and in nonmycorrhizal and mycorrhizal roots of chicory (Cichorium intybus), leek (Allium porrum), and big bluestem (Andropogon gerardii). The lipids were analyzed by shotgun lipidomics using a high-resolution hybrid mass spectrometer. Size range between 1350 and 1550 Da was chosen for the detection of potential biomarkers among cardiolipins (1,3-bis(sn-3'-phosphatidyl)-sn-glycerols), a specific class of phospholipids. The analysis revealed a variety of molecular species, including cardiolipins containing one or two polyunsaturated fatty acids with 20 carbon atoms each, i.e., arachidonic and/or eicosapentaenoic acids, some of them apparently specific for the mycorrhizal samples. Although further verification using a greater variety of AM fungal species and samples from various soils/ecosystems/environmental conditions is needed, current results suggest the possibility to identify novel biochemical signatures specific for AM fungi within mycorrhizal roots. Whether they could be used for quantification of both root and soil colonization by the AM fungi merits further scrutiny.
Keywords: houby; rostliny; česneky; kardiolipiny; Onions; Biomarker; ekosystém; Root colonization; uhlík; Shotgun lipidomics; Plant Roots; Fungi; Plants; půda; Extraradical mycelium; Carbon; kořeny rostlin; Mycorrhizae; mykorhiza; Quantification; Cardiolipins; Ecosystem; Soil